2020
DOI: 10.3390/foods9111533
|View full text |Cite
|
Sign up to set email alerts
|

Functional Food from Endangered Ecosystems: Atriplex portulacoides as a Case Study

Abstract: Biodiversity is a reservoir of potential sources of novel food and feed ingredients with suitable compositions for the improvement of the diet and well-being of humans and farmed animals. The halophyte Atriplex portulacoides occurs in habitats that are exposed to seawater inundations, and shows biochemical adaptations to saline and oxidative stresses. Its composition includes long chain lipids, sterols, phenolic compounds, glutathione and carotenoids. These organic compounds and micronutrients, such as Fe, Zn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 94 publications
(144 reference statements)
0
15
0
Order By: Relevance
“…This paper focuses on the species Halimione portulacoides (L.) Aellen (a.k.a. sea purslane), an edible halophyte relatively widespread throughout European and Mediterranean saltmarshes with traditional human uses [15] whose aquaculture and nutritional potential has only recently been scientifically explored [16][17][18][19][20][21]. These first studies showed that H. portulacoides has one of the highest productivity rates among studied halophytes in saline hydroponic conditions and can contribute to the substantial removal of dissolved inorganic N and P, up to a rate of approximately 4.0 mg N g −1 and 0.4 mg P g −1 [16].…”
Section: Introductionmentioning
confidence: 99%
“…This paper focuses on the species Halimione portulacoides (L.) Aellen (a.k.a. sea purslane), an edible halophyte relatively widespread throughout European and Mediterranean saltmarshes with traditional human uses [15] whose aquaculture and nutritional potential has only recently been scientifically explored [16][17][18][19][20][21]. These first studies showed that H. portulacoides has one of the highest productivity rates among studied halophytes in saline hydroponic conditions and can contribute to the substantial removal of dissolved inorganic N and P, up to a rate of approximately 4.0 mg N g −1 and 0.4 mg P g −1 [16].…”
Section: Introductionmentioning
confidence: 99%
“…This plant is dispersed along the coast of the Iberian Peninsula, and the prevalence in the Portuguese estuaries is at Tagus and Ria de Aveiro salt marches [7][8][9][10]. With a controversial taxon background, Atriplex portulacoides is also acknowledged as a senior synonym of Halimione portulacoides in the International Plant Names Index [11]. This plant is characterized as a shrub, reaching up to 1.5 m in height (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The lipophilic fraction of H. portulacoides leaves from estuarine environments of Portugal is mainly composed of long-chain aliphatic acids (e.g., octacosanoic, triacontanoic, oleic, hexadecanoic, and linoleic) and alcohols (e.g., octacosanol, hexacosanol, and triancontanol) (both in the C16-C30 range) while containing smaller amounts of sterols, such as schottenol, sitosterol, and sitostanol. Furthermore, the environmental stresses induce in a plant the synthesis of a wide range of phenolic compounds, such as sulfated flavonoids, particularly derivatives of isorhamnetin-sulfate and carotenoids (such as zeaxanthin, βcarotene, lutein, auroxanthin, violaxanthin, and antheraxanthin) [11,[14][15][16][17][18]. These confer important biological properties, such as antioxidant, anti-inflammatory, anti-trombotic, and anti-cancerogenic activities [4,11,18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations